The enigmatic tropical alpine flora on the African sky islands is young, disturbed, and unsaturated - Kandziora, Martha; Gehrke, Berit; Popp, Magnus; Gizaw, Abel; Brochmann, Christian; Pirie, Michael D (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Tropical alpine floras are renowned for high endemism, spectacular giant rosette plants testifying to convergent adaptation to harsh climates with nightly frosts, and recruitment dominated by long-distance dispersal from remote areas. In contrast to the larger, more recent (late Miocene onward) and contiguous expanses of tropical alpine habitat in South America, the tropical alpine flora in Africa is extremely fragmented across small patches on distant mountains of variable age (Oligocene onward). How this has affected the colonization and diversification history of the highly endemic but species-poor afroalpine flora is not well known. Here we infer phylogenetic relationships of ∼20% of its species using novel genome skimming data and published matrices and infer a timeframe for species origins in the afroalpine region using fossil-calibrated molecular clocks. Although some of the mountains are old, and although stem node ages may substantially predate colonization, most lineages appear to have colonized the afroalpine during the last 5 or 10 My. The accumulation of species increased exponentially toward the present. Taken together with recent reports of extremely low intrapopulation genetic diversity and recent intermountain population divergence, this points to a young, unsaturated, and dynamic island scenario. Habitat disturbance caused by the Pleistocene climate oscillations likely induced cycles of colonization, speciation, extinction, and recolonization. This study contributes to our understanding of differences in the histories of recruitment on different tropical sky islands and on oceanic islands, providing insight into the general processes shaping their remarkable floras.
Keywords: rostliny; age of flora; extinction; Climate Change; ekosystém; molecular dating; genetická variace; Islands; klimatické změny; tropical alpine habitats; Plants; Genetic Variation; východní Afrika; Africa, Eastern; populace; Humans; ostrovy; Population; Ecosystem; lidé